The Effect of Complexity of Fuel Oil Composition Compounds on Desulphurization Degrees in Oxidative Desulphurization Processes - Rofii, Mochammad; Nasikin, Mohammad (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Oxidative Desulfurization is an alternative process to reduce sulfur content in fuel. ODS is an oxidation reaction of sulfur compounds in fuel, which contains various hydrocarbon compounds, using an oxidizing agent with the help of a catalyst. The polarity of fuel, sulfur compounds and catalysts is a critical success factor for ODS. This study aims to determine the effect of the complexity of the model fuel used in the ODS process on the degree of sulfur reduction. The complexity variable is considered by polarity, which is determined based on the dielectric constant of the compound using the mixed concentration average of the dielectric constant of the pure compound. The model fuel used in this study is a mixture of hydrocarbon compounds having 6 C atoms in the form of n-hexane, cyclohexane, and benzene. Dibenzothiophena is used as a representative of sulfur compounds with an initial concentration of 300 ppm in each sample. The independent variables that were varied were the composition of the model fuel and the ODS reaction time. Sulfur content in model fuel before and after ODS was analyzed using UV-Vis. Meanwhile, the dielectric constants of fuel and catalyst are determined using empirical equations. The results showed that the polarity of the model fuel changed depending on the composition of the constituent compounds. The ODS process resulted a decrease in DBT levels as a function of increasing the time reaction of ODS. Changes in the polarity of the model fuel solvent give different desulphurization results. The highest degree of desulphurization was obtained at 21% with the use of model fuel with a catalyst which had a dielectrict constant of 1.995.